An Evaluation of Three Different Cranial Cruciate Ligament Surgical Stabilization Procedures As They Relate to Postoperative Meniscal Injuries - Metelman, A. Lisa; Schwarz, P. D.; Salman, M.; Alvis, M. R. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
Cranial cruciate ligament (CrCL) rupture is the most commonly diagnosed stifle condition in the dog. Meniscal injury, in conjunction with CrCL rupture is also common in both man and dogs. There is a growing concern regarding meniscal injuries, whether unrecognized at the time of CrCL surgical stabilization or subsequent to stabilization, and the relationship to poor postoperative functional outcome. However, current literature is not specific as to an actual number of dogs subsequently requiring a second arthrotomy/meniscectomy.Three different CrCL stabilization operations in dogs were compared, retrospectively, for the occurrence of post-operative meniscal damage requiring a second arthrotomy and meniscectomy. Additional information concerning: signalment, weight, history of injury, CrCL ruptured, surgeon, type of CrCL rupture and amount of arthritis present was recorded in 665 cases. It was found that 13.8% of the stifles at risk (i. e. those stifles that did not have the meniscus removed at the time of initial surgical stabilization) returned for a second arthrotomy/meniscectomy. A significant difference in outcome was not found between the results when initially performed by different surgeons. The number of dogs which returned for a second arthrotomy/ meniscectomy whose weight were ≤ 15 kg was significant, when compared to the total number of dogs considered at risk for this weight range. There was a significantly lower rate of return, in those dogs at risk, which had received fibular head transposition stabilization.A retrospective study of 665 canine cranial cruciate ligament rupture cases documents the incidence (13.8%) of those dogs requiring a second arthrotomy, and subsequent meniscectomy, after one of three initial surgical stabilization procedures. Of the three procedures, the fibular head transposition technique had a significantly lower return rate requiring subsequent meniscectomy.
Keywords: Meniscectomy; cranial cruciate ligament; canine